Magnetisation transfer ratio and mean diffusivity of normal appearing white and grey matter from patients with multiple sclerosis - Cercignani, M; Bozzali, M; Iannucci, G; Comi, G; Filippi, M (Journal of neurology, neurosurgery and psychiatry, 2001)
OBJECTIVE To assess the feasibility of a new technique based on diffusion anisotropy to segment white and grey matter of the brain. To use this technique to measure the mean diffusivity (D̄) and magnetisation transfer ratio (MTR) of normal appearing white matter (NAWM) and grey matter (NAGM) from patients with multiple sclerosis. METHODS Dual echo turbo spin echo, MT, and diffusion weighted scans of the brain were obtained from 30 patients with multiple sclerosis and 18 sex and age matched healthy controls. After image coregistration and removal of T2 visible lesions, white and grey matter were segmented from 10 supratentorial slices using diffusion anisotropy thresholds. Histograms of the average MTR and D̄ were created for normal white and grey matter of controls and NAWM and NAGM of patients with multiple sclerosis. RESULTS All the MTR histogram derived metrics of the NAWM from patients with multiple sclerosis were significantly lower than those of white matter from controls. The peak height of the D̄histogram of NAWM from patients with multiple sclerosis was also significantly different from that of normal white matter. The average MTR, the peak location of the MTR histogram, and peak height of theD̄ histogram of the NAGM of patients with multiple sclerosis were significantly lower than the corresponding quantities of grey matter from controls. CONCLUSIONS A technique was developed for segmenting white and grey matter with the potential for improving the understanding of the pathophysiology of many neurological conditions. Its application to the study of multiple sclerosis confirms the presence of a diffuse tissue damage in the NAWM of these patients and suggests that subtle changes also occur in the NAGM.